2015
DOI: 10.1088/0953-4075/48/16/164003
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiomultiple spawning on laser-dressed states: a study of 1,3-cyclohexadiene photoisomerization via light-induced conical intersections

Abstract: We extend the ab initio multiple spawning method to include both field-free and field-induced nonadiabatic transitions. We apply this method to describe ultrafast pump-probe experiments of the photoinduced ring-opening of gas phase 1,3-cyclohexadiene. In the absence of a control field, nonadiabatic transitions mediated by a conical intersection (CoIn) lead to rapid ground state recovery with both 1,3-cyclohexadiene and ring-opened hexatriene products. However, application of a control field within the first 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 68 publications
1
54
0
Order By: Relevance
“…38,39 Such a large QY, which however could have been affected by a rather poor time resolution of early diffraction experiments, was in striking contrast to the results of electronic structure calculations, which rather consistently predicted a yield similar to the one shown for the reaction in solution. 14,[21][22][23][25][26][27][28][29][30] Two later experiments provided an indirect evidence of a non-unit QY in the gas phase (50% 40 and an upper bound of 73% 41 ) and finally Adachi et al estimated it as low as 30% by fitting the observed differential photoelectron spectra (averaged over the time range of 510 − 990 fs after initial excitation) into the estimated ones based on He(I) photoelectron spectra. 11 The nature of the observed branching ratio is not clear either and has been attributed to the local PES topology around the S 1 /S 0 CoIn and its location on a hypersurface, 14,22 extended crossing seam, 19 sufficient wavepacket momentum, 26 gained along the stretching carbon-carbon bond 30,42 or more generally along the bond-alternating coordinate.…”
Section: Reaction Coordinatementioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Such a large QY, which however could have been affected by a rather poor time resolution of early diffraction experiments, was in striking contrast to the results of electronic structure calculations, which rather consistently predicted a yield similar to the one shown for the reaction in solution. 14,[21][22][23][25][26][27][28][29][30] Two later experiments provided an indirect evidence of a non-unit QY in the gas phase (50% 40 and an upper bound of 73% 41 ) and finally Adachi et al estimated it as low as 30% by fitting the observed differential photoelectron spectra (averaged over the time range of 510 − 990 fs after initial excitation) into the estimated ones based on He(I) photoelectron spectra. 11 The nature of the observed branching ratio is not clear either and has been attributed to the local PES topology around the S 1 /S 0 CoIn and its location on a hypersurface, 14,22 extended crossing seam, 19 sufficient wavepacket momentum, 26 gained along the stretching carbon-carbon bond 30,42 or more generally along the bond-alternating coordinate.…”
Section: Reaction Coordinatementioning
confidence: 99%
“…[5][6][7][8][9][10][11] Experimental findings have been supported by theoretical calculations, including study of potential energy surface (PES) critical points, 7,[12][13][14][15][16][17][18][19] restricted-dimensional quantum dynamical, [20][21][22][23] and fulldimensional mixed quantum-classical trajectory-based simulations. [24][25][26][27][28][29][30] Until recently, the explicit evolution of geometry following photoexcitation could be obtained only from potential surfaces derived from electronic structure calculations; recent advances in ultrafast X-ray sources with high intensity and electron diffraction techniques have allowed for the first direct insights into the sub-picosecond imaging of CHD photodissociation. [31][32][33] The first X-ray spectroscopic study to directly reveal the valence electronic structure of the transient pericyclic minimum predicted by Lugt and Oosterhoff has also been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Strong coupling to one or more radiation field modes can alter the molecular levels, profoundly affecting the basic photophysical and photochemical processes. The obvious way to achieve this regime is by subjecting the molecule to strong laser fields 4,[17][18][19] . Alternatively the coupling can be enhanced by placing the molecule in a cavity and letting it interact with the localized cavity modes.…”
Section: Introductionmentioning
confidence: 99%
“…20 Besides the diatomic studies, a few results are available for polyatomics as well. [21][22][23][24] In this case, due to the presence of several vibrational degrees of freedom, LICI can form without rotation, which opens up the door for manipulating and controlling nonadiabatic effects by light.…”
Section: Introductionmentioning
confidence: 99%